Step-by-step explanation:
I guess, the question is, how many miles were driven ?
if that is the case, then
we need to deduct the basic fee of $14.75, as this would have been paid, even if they did not drive a single mile.
so, 50.45 - 14.75 = $35.70
that is the actual cost for the driven miles.
how many miles ?
well, how often do $0.15 fit into $35.70 ?
35.7 / 0.15 = 238 miles.
this customer had been driving the moving van for 238 miles.
3 ft is less than 21 ft
(if you ment 21 inches 3ft=36 inches so if you ment that 3 ft would be larger in that case)
Answer:
Four hundred Thirty-three and thirty-eight hundredths
Step-by-step explanation:
the four is four hundred
the two three's after the four are thirty-three
and the three and eight after the decimal are thirty-eight hundredths
Answer:
Quadrant 4
Step-by-step explanation:
If the given angle was positive, then we go clockwise.
But it's negative so we go counterclockwise.
An alternative way of graphing
Quadrant 1 is 0-90°
Quadrant 2 is 90-180°
Quadrant 3 is 180-270°
Quadrant 4 is 270-360°
Subtract the given angle by 360 until no longer possible
750 - 360 = 390 390 - 360 = 30
Remember that this was originally a negative angle
Instead of going clockwise to quadrant 1, we go counterclockwise to quadrant 4, ending up at 330°
Answer:
¬(W∨S)→¬(J∨E)
D→(B∨C)
X is true
No
Step-by-step explanation:
The hypotheses "neither water nor soft drinks can quench your thirst" translates to ¬(W∨S) ("neither nor" negates the disjunction W∨S). The "if,... then" translates to the implication symbol (arrow). The conclusion "juice will not do it, unless the juice contains electrolytes" translates to ¬(J∨E). This is because if J or E were true, then J would be true (because E implies J), contrary to the conclusion that J is false ("juice will not do it"), then J∨S is false.
The hypothesis here is "the dyer breaks" hence D is the hypothesis. The conclusion is "we will hang the clothes to dry, or take the clothes to a coin-operated laundry" which is the same as (B∨C).
The proposition p→p is always true (according to truth tables). In this case, p:=X is true, then p is true and X is true.
X∨Y is false if and only if X is false and Y is false, so both statements X,Y must be false.